Od opowieści do modlitwy. Wokół wiersza Rorate coeli Andrzeja Buszy - Ożóg, Zenon (Dydaktyka Polonistyczna, 2018)
The author analyses and interprets the poem Rorate coeli by Andrzej Busza within two main contexts: firstly, the origin and poetic realisation of the Advent motif „rorate coeli desuper”, secondly, the structure of psalm as a literary genre, which has fixed indicators of a prayer, including a poetic prayer (invocation, petition, the subject of request). A significant role in the poem is played not only by performatives (request), but also sentences describing the spiritual status of the lyrical subject, which can be interpreted as the act of complaint directed to God.